Highest record for the lizard Phymaturus palluma (Squamata: Liolaemidae) in Central Andes, Argentina - Vicenzi, Nadia Pamela (2017)
We have identified individuals of Phymaturus palluma at 3800 masl in Aconcagua Provincial Park, Mendoza, Argentina. Altitudinal distribution of the species previously known was from 1400 to 2200 masl. This represents the uppermost distributional record extending the current range of the species 1600 m of elevation.